2023
DOI: 10.1364/boe.488453
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tissue fixation on the optical properties of structural components assessed by non-linear microscopy imaging

Abstract: Fixation methods such as formalin are commonly used for the preservation of tissue with the aim of keeping their structure as close as possible to the native condition. However, fixatives chemically interact with tissue molecules, such as collagen in the extracellular matrix (ECM) or myosin, and may thus modify their structure. Taking advantage of the second- and third-harmonic generation (SHG and THG) emission capabilities of such components, we used nonlinear two-photon microscopy (NL2PM) to evaluate the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…However, we found that the beam profiles measured in the mouse cortex were significantly larger than the beam width predicted in the scattering simulation presented in Section S2. We speculate that one reason for this difference is the use of fixed tissue, which can have a higher optical scattering than fresh samples, as reported in [41,42]. Further evidence of this hypothesis is provided by the improved agreement between the experimental and simulated beam widths when using higher scattering coefficient settings in the simulation.…”
Section: Discussionmentioning
confidence: 72%
“…However, we found that the beam profiles measured in the mouse cortex were significantly larger than the beam width predicted in the scattering simulation presented in Section S2. We speculate that one reason for this difference is the use of fixed tissue, which can have a higher optical scattering than fresh samples, as reported in [41,42]. Further evidence of this hypothesis is provided by the improved agreement between the experimental and simulated beam widths when using higher scattering coefficient settings in the simulation.…”
Section: Discussionmentioning
confidence: 72%
“…This method generates specific signals for structures such as collagen and myosin without the need for labelling. Depending on the properties of the excitation laser, the maximum possible imaging depth can range between 100 µm and 1,000 µm; however, this method performs poorly in paraffinembedded tissue (32). While the contrast produced in SRµCT is not specific to histologic features, the placement of the histologic slice into the 3D µCT context, as shown here, provides sufficient "starting point" information for extrapolation, which is a good alternative to the aforementioned methods.…”
Section: Discussionmentioning
confidence: 98%